Peningkatan Kemampuan Pemecahan Masalah Matematis Pada Soal Cerita Matematika Kelas V Melalui Media “Puzzle Cermat” - Reskinda Ramandani; Hasna Dyah Ekaputri; Diana Ermawati (Journal Innovation In Education, 2024)
This research aims to improve mathematical problem solving abilities in mathematics story problem using the Smart Puzzle media. In this research, the material used in learning word problems was multiplication and divison of fractions for fifth grade elementary school students. Data collection was carried out at SD Negeri Pat Lor 05 with 22 students in class V elementary school. The type of research used is Classroom Action Research (PTK) which consists of II cycles, each cycle is held in 2x meetings. This research data was obtained through interviews, observations and tests. The test data resulting from mathematical problem solving abilities were analyzed based on the percentage of individual mathematical problem solving completeness. The analysis techniques used in this study are qualitative data analysis and quantitative data analysis. The results of the research showed that research showed that there was an increase in the percentage in cycles I and II obtained by class V students. This was shown by the students mathematical problem solving abilities referring to predetermined success criteria. The average score for cycle I was 70,3%, increasing in cycle II to 83,9%, an increase also occurred in the scores of students who had reached the KKM (80), namely increasing from 59% to 90,9%. Based on the results obtained, it can be conclude that learning using the Careful Puzzle media can improve the mathematical problem olving abilities of class V students at Pati Lor 05 Elementary School.